2008
DOI: 10.1159/000121381
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Chiari I Malformation and Syringomyelia after Valveless Lumboperitoneal Shunt in Infancy

Abstract: The authors present the case of a 13-year-old boy who experienced frequent disabling episodes of typical postural induced headaches, which revealed a Chiari I malformation, syringomyelia and cervical spinal cord edema. This boy had received a valveless lumboperitoneal (LP) shunt at the age of 18 months for macrocephaly. At this time, cranial CT scan showed moderate enlargement of the subarachnoid spaces without hydrocephalus or tonsillar herniation. The LP shunt was clamped but the patient experienced signs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…6,13 Acquired CM-I has also been described in infants, particularly after lumbar puncture or placement of a lumboperitoneal shunt. 10 It should be noted that the first twin in the present study did undergo a lumbar puncture although only a small volume of cerebrospinal fluid was obtained for diagnostic purposes (< 1.5 ml); this . The initial MR imaging shows the cerebellar tonsils to be elongated and peg-shaped.…”
Section: Discussionmentioning
confidence: 77%
“…6,13 Acquired CM-I has also been described in infants, particularly after lumbar puncture or placement of a lumboperitoneal shunt. 10 It should be noted that the first twin in the present study did undergo a lumbar puncture although only a small volume of cerebrospinal fluid was obtained for diagnostic purposes (< 1.5 ml); this . The initial MR imaging shows the cerebellar tonsils to be elongated and peg-shaped.…”
Section: Discussionmentioning
confidence: 77%
“…A previous study reported a slight female predominance (female/male ratio 1.3:1.0) (20), although this is inconsistent with the findings in the current study (female/male ratio 1.00:1.52). CM-I is generally considered a congenital neurological condition, although in recent years its acquired form has been identified as a complication of CSF diversion procedures or chronic CSF leakage (21,22). CM-I is thought to be a multifactorial condition, although the pathogenesis is still undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…Laurent Riffaud et al observed that the valveless LP shunt may expose the patient to the risk of symptomatic ACM and syringomyelia. They suggested LP shunt with an adjustable valve to prevent such complications (23). Roger Strachan et al observed that the catheter length and placement are important in reducing the risk of low pressure symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…We used Chhabra system without valve and a catheter length of 7-10 cms was not associated with any permanent over drainage complication. Programmable shunt can also reduce over drainage complications (19,23).…”
Section: Resultsmentioning
confidence: 99%